Thirty Years of Information Research - Fulton, Crystal; Dillen, Wout (Information Research an international electronic journal, 2025)
April 2025 marked the 30th year anniversary of Information Research. To celebrate this occasion, the current issue of the journal is a special issue, filled with short contributions commemorating the impact the journal and its founder have had on the research field and its practitioners.